The efficacy and safety of lenalidomide plus dexamethasone in relapsed and/or refractory multiple myeloma patients with impaired renal function - Dimopoulos, Meletios A.; Alegre, Adrian; Stadtmauer, Edward A.; Goldschmidt, Hartmut; Zonder, Jeffrey A.; de Castro, Carlos M.; Masliak, Zvenyslava; Reece, Donna; Olesnyckyj, Marta; Yu, Zhinuan; Weber, Donna M. (Cancer, 2010)
Background: In patients with multiple myeloma, renal impairment (RI) at the time of diagnosis is associated with poor survival. To the authors' knowledge, the current retrospective analysis presented is the first to assess the impact of various degrees of renal dysfunction on safety and efficacy outcomes in a large cohort of patients with relapsed and/or refractory multiple myeloma who received treatment with lenalidomide plus dexamethasone. Methods: Three hundred fifty-three patients from 2 large phase 3 trials were randomized to receive lenalidomide (25 mg) plus dexamethasone (40 mg). For the purpose of this analysis, RI was defined according to the calculated creatinine clearance (CLCr) level as follows: mild or no RI (CLCr ≥ 60 mL/minute), moderate RI (CLCr from ≥ 30 mL/minute to <60 mL/minute), and severe RI (CLCr <30 mL/minute). Results: The RI subgroups did not differ significantly in terms of the overall response rate (range, 50%-64%) or response quality (very good partial response or better, 27%-37%). In all RI subgroups, the time to progression and progression-free survival did not differ significantly compared with the mild or no RI group. Patients with RI experienced an increased incidence of thrombocytopenia, required more frequent lenalidomide dose reduction or interruption, and had shorter overall survival than patients with mild or no RI (P = .006). Lenalidomide plus dexamethasone led to improvement in renal function in the majority of patients. Conclusions: The results from this study indicated that, with careful monitoring of the CLCr level and adverse events as well as appropriate dose adjustments, lenalidomide plus dexamethasone is an effective and well tolerated treatment option for patients with multiple myeloma who have RI.
Gesehen am 06.02.2023